2000
DOI: 10.1080/713688913
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Cystic Tumor of the Pancreas Coexisting With Hairy Cell Leukemia

Abstract: The coexistence of a pancreatic papillary cystic tumor with hairy cell leukemia is reported. To the best of our knowledge this association has never been published. A 41-year-old man diagnosed with hairy cell leukemia developed a second malignancy that corresponded to a papillary cystic pancreatic tumor. The patient underwent splenectomy and a tumoral surgical resection, and is currently well at 21 months follow-up. A pathogenetic relationship between the two malignancies was not demonstrated. Hairy cell leuke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A case report reported by Acebo et al examined a patient that presented with papillary cystic tumour of the pancreas with coexisting HCL. 3 The patient in this case report was diagnosed with HCL and then 7 months later was found to have papillary cystic tumour of the pancreas. After going through a thorough literature review, they found no association between the two cancers and treatment consisted of tumour resection, followed by treatment for HCL with purine analogues.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…A case report reported by Acebo et al examined a patient that presented with papillary cystic tumour of the pancreas with coexisting HCL. 3 The patient in this case report was diagnosed with HCL and then 7 months later was found to have papillary cystic tumour of the pancreas. After going through a thorough literature review, they found no association between the two cancers and treatment consisted of tumour resection, followed by treatment for HCL with purine analogues.…”
Section: Discussionmentioning
confidence: 76%
“…A case report reported by Acebo et al examined a patient that presented with papillary cystic tumour of the pancreas with coexisting HCL 3. The patient in this case report was diagnosed with HCL and then 7 months later was found to have papillary cystic tumour of the pancreas.…”
Section: Discussionmentioning
confidence: 87%